Security of Mobile ad-hoc Wireless Networks. A Brief Survey - TILIUTE, D. E. (Advances in Electrical and Computer Engineering, 2007)
One of the most present issues of computer wireless networks is the security. Comparing with their wired counterpart, the wireless networks not only accentuate some of the well-known security vulnerabilities but they are subject of new and specific ones. Among the existing wireless networks the ad hoc ones are the most exposed to attacks and collusions due to the absence of any centralized control. The most efficient way to ensure the communication secrecy, inclusively for ad hoc wireless networks, is the cryptography. From many reasons, following from specific operating conditions, the employment of asymmetric key techniques and Public Key Infrastructure is not a realistic choice. In the networks with a large number of nodes, as wireless sensor networks, a large number of secret keys are involved in order to ensure the communication secrecy. While dynamicity is one of the essential features of mobile wireless networks, when nodes may leave or join the network and in the absence of a centralized control entity, the management of secret keys is crucial. The paper presents the main aspects of mobile wireless networks security and focuses on the key management issue in ad-hoc wireless networks.